2018
DOI: 10.1186/s12886-018-0996-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted antioxidant SKQ1 protects cornea from oxidative damage induced by ultraviolet irradiation and mechanical injury

Abstract: BackgroundCornea protects the eye against natural and anthropogenic ultraviolet (UV) damage and mechanical injury. Corneal incisions produced by UV lasers in ophthalmic surgeries are often complicated by oxidative stress and inflammation, which delay wound healing and result in vision deterioration. This study trialed a novel approach to prevention and treatment of iatrogenic corneal injuries using SkQ1, a mitochondria-targeted antioxidant approved for therapy of polyethiological dry eye disease.MethodsRabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Although the exact mechanism underlying this protective effect has not yet been elucidated, several in vitro and animal studies have suggested a relationship between free radical scavengers and reduced CEC damage. 43,44 Cestmir et al and Guo-Jian et al reported that antioxidants play an important role in the survival, healing, and migration of CEC. 45, double-blind clinical trial indicating that the use of dissolved H 2 in irrigation solution reduced corneal endothelial damage during phacoemulsification.…”
Section: Accepted Articlementioning
confidence: 99%
“…Although the exact mechanism underlying this protective effect has not yet been elucidated, several in vitro and animal studies have suggested a relationship between free radical scavengers and reduced CEC damage. 43,44 Cestmir et al and Guo-Jian et al reported that antioxidants play an important role in the survival, healing, and migration of CEC. 45, double-blind clinical trial indicating that the use of dissolved H 2 in irrigation solution reduced corneal endothelial damage during phacoemulsification.…”
Section: Accepted Articlementioning
confidence: 99%
“…The total antioxidant activity in AH was analyzed via hemoglobin/H 2 O 2 /luminol system, as described in our previous works [68][69][70]. Briefly, the AH samples were diluted 200-fold with PBS and added to the reaction mixture, containing 0.01 mm luminol and 0.5 mm hemoglobin.…”
Section: Total Antioxidant Activity Analysismentioning
confidence: 99%
“…130 It can also inhibit oxidative stress, effectively prevent damage caused by ultraviolet light, and promote corneal wound healing after eye surgery. 131 Collectively, these studies suggest that SKQ1 has the potential to become an effective antioxidant and a promising drug promoting healthy aging.…”
Section: Therapeutic Drugs Targeting Senescencementioning
confidence: 99%